2022
DOI: 10.4993/acrt.30.55
|View full text |Cite
|
Sign up to set email alerts
|

Baseline QOL, QOL-relevant HLA-restricted HERV gene-derived peptides, and survival outcomes in gastric cancer

Abstract: Introduction: Whether good baseline quality of life (QOL) is linked to improved QOL: improved overall survival (OS) which is relevant to HLA-restricted peptides has not been evaluated, and the causal nature of this correlation is not known. Methods: Pretreatment patient-reported QOL using the QOL-20 questionnaire and blood human leukocyte antigens (HLAs) was examined in 437 and 325 gastric cancer (GC) patients, respectively. We focused on the similarity between human endogenous retrovirus (HERV) and human immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…and influencing biological processes, such as early embryonic development 8) . We previously reported that in gastric cancer (GC), HLA-restricted HERV gene-derived peptides that predicted treatment responsiveness and survival 9) were also associated with quality of life (QOL) status and survival 10) . Moreover, the occurrence of some peptides increased with age but decreased after age 65 10) .…”
Section: Incidence Of Multiple Primary Malignancies Human Leukocyte A...mentioning
confidence: 99%
See 2 more Smart Citations
“…and influencing biological processes, such as early embryonic development 8) . We previously reported that in gastric cancer (GC), HLA-restricted HERV gene-derived peptides that predicted treatment responsiveness and survival 9) were also associated with quality of life (QOL) status and survival 10) . Moreover, the occurrence of some peptides increased with age but decreased after age 65 10) .…”
Section: Incidence Of Multiple Primary Malignancies Human Leukocyte A...mentioning
confidence: 99%
“…For subsequent analyses, two age group comparisons (<60 vs. ≥60 years and <65 vs. ≥65 years) were used. The former is the mean age in this study and the latter is based on a previous study 10) .…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation